2000
DOI: 10.1029/1999ja900475
|View full text |Cite
|
Sign up to set email alerts
|

High‐latitude ionospheric response to a sudden impulse event during northward IMF conditions

Abstract: A high‐density structure under northward interplanetary magnetic field BZ conditions is identified at the Wind and IMP 8 satellites, both in the solar wind on August 22, 1995. A compression of the magnetosphere is observed by the GOES 7 magnetometer within a few minutes of the pressure increase encountering the magnetopause. The response of the high‐latitude ionosphere is analyzed on the basis of ground‐based magnetometer data. A comprehensive description of this response in the Northern Hemisphere is provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
46
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 25 publications
13
46
1
Order By: Relevance
“…Engebretson et al (1999) showed equivalent convection patterns calculated from all available magnetometer data for the preliminary impulse and revealed traveling convection vortices (TCV). Moretto et al (2000) interpreted the response measured by ground-based magnetometers to a compression of the magnetosphere on 22 August 1995 in terms of potential patterns by means of the assimilative mapping of ionospheric electrodynamics (AMIE) technique (Richmond and Kamide, 1988). Slinker et al (1999) studied the ionospheric response to a density pulse in the solar wind using a global 3-D MHD model.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Engebretson et al (1999) showed equivalent convection patterns calculated from all available magnetometer data for the preliminary impulse and revealed traveling convection vortices (TCV). Moretto et al (2000) interpreted the response measured by ground-based magnetometers to a compression of the magnetosphere on 22 August 1995 in terms of potential patterns by means of the assimilative mapping of ionospheric electrodynamics (AMIE) technique (Richmond and Kamide, 1988). Slinker et al (1999) studied the ionospheric response to a density pulse in the solar wind using a global 3-D MHD model.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies mentioned above did not account for the IMF orientation (e.g., Lysak and Lee, 1992;Engebretson et al, 1999), some studies specifically focused on pressure changes when the IMF was northward (e.g., Russell and Ginskey, 1995;Slinker et al, 1999;Moretto et al, 2000;Fujita et al, 2003a,b). Using the University of Michigan MHD code, we have investigated the response of the magnetosphere-ionosphere system to a sudden pressure enhancement under northward IMF conditions and found the same responses as those reported by Slinker et al (1999), Keller et al (2002), Fujita et al (2003a), Fujita et al (2003b).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is known (e.g., (Moretto et al, 2000;Lukianova, 2004)) that the approach of the solar wind dynamic pres sure jumps to the Earth's magnetosphere affects the dis tribution of large scale ionospheric plasma convection at high latitudes. The data of the SuperDARN ground radar system (http://vt.superdarn.org/tiki index.php?page= Conv+map+overview), including the polar convec tion maps obtained by synthesizing the incoherent scatter radar observations and the known statistical models (e.g., (Cousins and Shepherd, 2010)), were used to consider variations in high latitude convection caused by dynamic pressure (Psw) jumps.…”
Section: Convection In the Polar Capmentioning
confidence: 99%